THE LEGAL PROTECTION OF THE RIGHTS OF THE SUSPECT IN THE CRIMINAL JUSTICE SYSTEM - Ihsan, Rifkah Auliah; Tahir, Heri; Agus, Andi Aco (Jurnal Aktor, 2025)
This study aims to analyze the application of legal protection of suspects' rights during the investigation stage in Makassar City, as well as to identify legal actions in the event of violations of these rights. The study uses a normative-empirical method with a regulatory-statutory and sociological approach. The regulatory-statutory approach is carried out through regulations, including the Criminal Procedure Code (KUHAP) and Law Number 39 of 1999 concerning Human Rights. The sociological approach is carried out through in-depth interviews with legal advisors and academics. The results of the study indicate that there are still violations of rights such as arrests and deportations without legal procedures, intimidation, and legal assistance. Legal actions or remedial measures that can be taken if violations occur include submitting a pretrial to the district court, reporting to the Professional and Security Division (Propam) of the Indonesian National Police for disciplinary violations, complaints to the National Commission on Human Rights in the event of human rights violations, and notification of follow-up actions regarding investigations that commit violence or. The research conclusion shows that legal protection does not fully reflect the principle of due process of law and requires strengthening supervision and the active role of legal advisors.